SUCCESSIVE SOLVENT EXTRACTION AND HPTLC OF STEM BARK OF ASOKA - SARACA ASOCA (ROXB.) DE WILDE - Raj, Asha S; Oommen, Sara Monsy (International Journal of Ayurveda and Pharma Research, 2018)
Asoka – Saraca asoca (Roxb.) de Wilde, is a medium sized evergreen tree growing in tropical regions. It has been used for various medicinal purposes from the time immemorial. Ample citations about its usage can be elicited from Veda’s, Puranas and Samhitas. Owing to extensive use, lack of cultivation and irrational collection practices it became an endangered drug. It’s one among the five endangered plants listed by NMPB. This scarcity of drug in the market eventually led to adulteration. It is one of the severely adulterated drug next to Bala – Sida species. Various pharmacognostical and phytochemical techniques are evolved from time to time to check the adulteration. Due to the sophisticated methodologies used by medicinal plant dealers, these methods fail to check adulteration. Pharmacognostical analysis of sample drug and its powder microscopy serves as an effective method to check adulteration. But it won’t serve fruitful when the drug gets adulterated with exhausted samples. In such cases, effective marker compounds of the drug need to be analysed. This can be achieved by analysing successive solvent extractives of test drug and by HPTLC analysis. Here an attempt has been done to analyse the successive solvent extraction and HPTLC of stem bark of Asoka – Saraca asoca (Roxb.) de Wilde. as an effective methodology to ensure the purity. The successive solvent extraction revealed 1.78%, 0.4%, 13.63% & 27.69% of extractives respectively in petroleum ether, cyclohexane, acetone and methyl alcohol. The qualitative analysis also showed significance difference in the steroids, alkaloids, phenols and flavonoids in each solvent. The results are promising and suggestive of considering these experiments as an effective method to ensure the quality and purity of drug sample.